Defects in semiconductors - Romano, Lucia, 1977-; Privitera, Vittorio; Jagadish, C. (Academic Press is an imprint of Elsevier, 2015)
This volume, number 91 in the Semiconductor and Semimetals series, focuses on defects in semiconductors. Defects in semiconductors help to explain several phenomena, from diffusion to getter, and to draw theories on materials' behavior in response to electrical or mechanical fields. The volume includes chapters focusing specifically on electron and proton irradiation of silicon, point defects in zinc oxide and gallium nitride, ion implantation defects and shallow junctions in silicon and germanium, and much more. It will help support students and scientists in their experimental and theoretical paths.
Keywords: Semiconductors -- Defects.; elektronické knihy; electronic books